Synthesis of Silica Nanoparticle Made from Lampung Pumice Modified with Sonication Parameters for Size and Purity - Siti Rahmadianti; Yusup Hendronursito (Jurnal Riset Teknologi Pencegahan Pencemaran Industri, 2023)
This study aims to determine the effect of sonication process parameters on the formation of the size and purity of silica from the synthesis of pumice. Pumice reflux process using NaOH for 24 hrs. Titrate using 5M H2SO4 solution to pH 7 and a white gel is formed. The residue was washed using distilled water and dried at 100 oC for 24 hrs. The residue was then stirred with 1M HCl solution for 4 hrs. After the synthesis process, the silica powder was then subjected to a sonication process with temperature variations of 30, 60, and 80 oC for 1, 2, and 3 hrs. The purity of silica was evaluated from the results of x-ray fluorescence, x-ray defragment, and SEM test results. The results of the analysis of variance showed that the independent variable temperature contributed 67.25% and had a significant effect on the SiO2 concentration. The two sonication variables, temperature and time, contributed 50.31% and 46.24%, respectively. The variables significant effect on particle size. Other independent variables affect the SiO2 concentration by 10.36%. The sonication process can increassed concentration and reduced particle size of silica synthesized by selecting the appropriate independent variable.